Synthetic Biology Reveals the Uniqueness of the RIP Kinase Domain - Chirieleison, Steven M; Kertesy, Sylvia B; Abbott, Derek W (The Journal of immunology (1950), 2016)
The RIP kinases (RIPKs) play an essential role in inflammatory signaling and inflammatory cell death. However, the function of their kinase activity has been enigmatic, and only recently has kinase domain activity been shown to be crucial for their signal transduction capacity. Despite this uncertainty, the RIPKs have been the subject of intense pharmaceutical development with a number of compounds currently in preclinical testing. In this work, we seek to determine the functional redundancy between the kinase domains of the four major RIPK family members. We find that although RIPK1, RIPK2, and RIPK4 are similar in that they can all activate NF-κB and induce NF-κB essential modulator ubiquitination, only RIPK2 is a dual-specificity kinase. Domain swapping experiments showed that the RIPK4 kinase domain could be converted to a dual-specificity kinase and is essentially indistinct from RIPK2 in biochemical and molecular activity. Surprisingly, however, replacement of RIPK2’s kinase domain with RIPK4’s did not complement a nucleotide-binding oligomerization domain 2 signaling or gene expression induction defect in RIPK2−/− macrophages. These findings suggest that RIPK2’s kinase domain is functionally unique compared with other RIPK family members and that pharmacologic targeting of RIPK2 can be separated from the other RIPKs.